Study of Analytical Characterization and Antibacterial Activity of Silver Nanoparticles Synthesized by Using Pineapple Juice as a Reducing Agent (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the past years, various phytosynthetic processes have been utilised of silver nanoparticles for the lowcost and environmentally friendly comparing to the chemical and physical methods. These unique metalnanoparticles are used in several applications which are including pharmaceuticals, antimicrobial andbiomedical applications. Wherefore, the object of this work is biosynthesizing AgNPs from extracts ofpineapple juice as reducing studying their characteristics by Ultraviolet-Visible (UV-vis) Spectrometer,Atomic Force Microscope (AFM), SEM Scanning Electron Microscope and Transmission ElectronMicroscope (TEM) The UV-Vis spectra results show a strong resonance centered on the surface of silvernanoparticles (AgNPs) at 410 nm. the presenting study is involved the preparation of (AgNPs) from naturalsource, which confirmed by UV-Visible spectral analysis in 410nm and the synergism effects with someantibiotic to increase the sensitivity to some pathogenic bacterial isolate as E. coli. In addition, our studyis presented results of the minimum inhibitory concentration (MIC) that MIC for AgNPs is 25 while otherantibiotics are (32,64,128). Finally, the synergism activity shows a significant difference in the sensitivity ofsome antibiotics used against E. coli bacteria, especially with levofloxacin and increased the inhibition form419 mm to 1657.2 mm.